Assessing the supply chain intelligence practices of small medium enterprises in Malaysia - Jaharuddin, Nor Siah; Mansor, Zuraina; Yaakob, Samsudin (Elsevier, 2016)
Small and medium enterprises (SMEs) represent the backbone of economic development of any country. In a turbulent dynamic market and changing environment, SMEs need to gain strategic information on its environments because failure to do so might pose a threat to firm's survival. Implementing supply chain intelligence (SCI) as a structured tool in gathering and analyzing information from 360-degree view of business activities is critical to businesses strategic decisions and performance in surviving and competing in dynamic markets. In spite of increasing interest and study in intelligence, discussion about the concept and its potential application to the SME sector was minimal from mainstream literature. Thus this study examines the level and extent of SCI practices amongst SMEs in strategic decisions and its contribution to enhance businesses and supply chain performance.